The Antimicrobial Activity of Silica Oxide Nanoparticles Against Some Bacteria and Fungi Isolates - Ghaidaa J. Mohammed (Journal of Global Pharma Technology, 2017)
The capability of some bacteria and fungi to resist common antibiotics has been a guide to discover new planning to treat the infections connected to antibiotic resistance in the patients. In this study, the antifungal and antibacterial activity of silica oxide nanoparticles was detected in vitro against some bacterial species (Klebsiella pneumonia, Staphylococcus aureus, Escherichia coli, Proteus mirabilis, and Pseudomonas aeroginosa) and some fungi (Aspergillus terrus, Aspergillus parasiticus, Aspergillus flavus, and Candida albicans) and contrasted with antibacterial antibiotics (Amikacin, Amoxillin, Augmastin, Cefotaxine, Ceftazidime, Ciprofloxacin, Gentamycin, Meropenum, and Tetracycline) and antifungal antibiotics (Amphotericin B and Ketoconazole). Silica oxide suspension was prepared by acetic acid solution. Results showed that concentrations of (10-40) µg/ml of silica oxide have antifungal and antibacterial activity against the tested microorganisms in this work more than antibiotics. In conclusion, Silica oxide relates superior antimicrobial characteristics.                       Keywords: Antimicrobial activity, Silica Oxide, Bacteria, Fungi.